Inquiry-Based Freshman Seminar on “What You Can (or Should Not) Do to End Global Poverty” - Kisaalita, William S. (Advances in Engineering Education, 2018)
Offering first year seminars and experiences is well-established as one of the high-impact educational practices. An inquiry-based freshman seminar in which students conduct poverty simulation term projects has been offered for five years at the University of Georgia. The students have four project options of: dressing the part and panhandling downtown or eating at a local soup kitchen, living on $5 per day for a reasonable number of days, and coming-up with their own similarly structured project. The key element in these projects is putting the student in the poor person’s shoes. The students reflect on their experiences through a 1000-word essay. To date, 73 students have taken the seminar: 31 students chose the panhandling project, 20 chose the $5 per day project, 18 chose the soup kitchen, and 4 chose the independent project. Qualitative analysis of the panhandling 35 reflections revealed seven themes, while analysis of the 38 $5 per day/soup kitchen reflections revealed eight themes. Some of these themes suggest the experience aroused the students’ empathetic (not sympathetic) feelings and thoughts. Of the 35 panhandling students, 20 exhibit the full extent of empathy. Of the 38 $5 per day/soup kitchen students, 29 exhibited the full extent of empathy. Full extent of empathy was counted from students who reported decisions they have or will make in response to the arousal. Whether these students will implement these decisions in the future or not is a question for a longitudinal follow-up study.